THE USE OF QUIZ METHOD TO INCREASE STUDENTS' LEARNING OUTCOMES OF DISCUSSION TEXT - Zakiah, Mutiara; Putera Jaya, Hariswan; Agustina, Sri (Jurnal PTK dan Pendidikan, 2023)
This study was Collaborative Classroom Action Research. This study was conducted at SMA Negeri 1 Palembang from February to April 2023 during the 2022/2023 academic year. There were 36 students of X.3 at SMA Negeri 1 Palembang as the subject in this study. The data collection in this study used observation, pre-test, and post-test. The data analysis technique used in this study was to compare students’ learning outcomes before and after the action in Cycle I and Cycle II. The objective of this study was to know the use of quiz method to increase students' learning outcomes of discussion Text. The result of this study showed that quiz method helps students' increase their learning outcomes.